Understanding the impacts of floods on learning quality, school facilities, and educational recovery in Indonesia. Issue 2 (23rd November 2022) - Lassa, Jonatan; Petal, Marla; Surjan, Akhilesh
Abstract : This research is among the first pieces of work to use the comprehensive school safety (CSS) framework to assess the impacts of floods on quality learning and education infrastructure. The CSS framework is employed here to identify the level of disruption to education services following floods in Jakarta, Indonesia, in 2013. The paper poses three key questions, concerning: (i) disruption to children's access to quality education during the flood emergency in 2013 and the early recovery phase; (ii) the impact of the floods on a school's physical infrastructure; and (iii) the effectiveness and level of success of the 2013 flood responses by relevant stakeholders. Combining quantitative and qualitative strategies, the paper examines the experiences of 100 schools in Jakarta. The findings suggest that the CSS framework offers a more nuanced approach to assessing post‐disaster education needs. Moreover, it is also relevant for examining the relationship between the COVID‐19 pandemic and relative losses in the education sector. المستخلص: هناك عجز في إطار تقييم آثار الكوارث الطبيعية، والتي منها الفيضانات، على القطاعات التعليمية. وهذا البحث هو من أحد أول المساعي لاتباع إطار الأمان المدرسي الشامل (CSS) لتقييم أثر الفيضانات على فقد جودة التعليم والبنية التحتية التعليمية. تم اتباع هذا الإطار لتحديد مستوى الاضطرابات في الخدمات التعليمية واستمرارية تأثرها بالفيضانات في العاصمة الإندونيسية. يطرح هذا المقال ثلاث أسئلة رئيسية: يطرح هذا البحث ثلاث أسئلة رئيسية، إلى أي مدى تؤدي حالة طوارئ من الفيضانات على نطاق واسع إلى تعطيل وصول الأطفال إلى تربية وتعليم جيديْن؟ والثاني، كيف يتكيف الأطفال والمعلمون والمدارس مع الاضطرابات والتأخيرات أثناء طوارئ الفيضانات؟ والثالث، كيف يمكن لسياسات إدارة الكوارث أن تساعد المدارس في التكيف والتعافي من الكوارث التي تتضمن الفيضانات؟ بخلط الاستراتيجيات/ الوسائل النوعية والكمية، يفحص هذا المقال تجارب 100 مدرسة في جاكارتا. تقترح نتائج البحث أن إطار الأمن المدرسي الشامل يوفر منهجاً أكثر وضوحاً لتقييم الحاجة التعليمية لما بعد الكارثة. نوصي أن هذا الإطار متصل بفحص أثر جائحة كوفيد‐19 على الخسائر النسبية في القطاع التعليمي. ونوصي أيضاً أن هذا الإطار يضع اللمسات الأخيرة على إطار تقييم الحاجات لما بعد الكارثة للقطاع التعليمي. الكلمات المفتاحية: الأمن المدرسي الشامل، تقليل مخاطر الكارثة، أثر الفيضان على المدارس، مخاطر الفيضان، إندونيسيا، جاكارتا، التعافي التعليمي، الاضطراب المدرسي، التعافي المدرسي 摘要: 自然灾害（包括洪水）对教育领域的影响一直缺乏系统的评估框架。该研究首次采用综合校园安全（CSS）框架来评估洪水对优质学习和教育基础设施损失的影响。研究采用CSS框架来确认印度尼西亚首都洪灾对教育服务的影响程度及影响的连续性。文章提出三个关键问题：问题一，大规模洪灾在多大程度上影响了儿童获得优质教育和学习的机会？问题二，儿童、教师和学校在突发洪水情况下，如何应对教学的中断和延误？问题三，灾害管理政策如何帮助学校应对洪水灾害和灾后恢复问题？结合定量和定性的策略，本文研究了雅加达100所学校的经历。研究结果表明，CSS框架为灾后教育需求评估提供了一个更细致的方案。我们认为，这个框架有利于研究新冠肺炎疫情对教育部门造成的相关损失。我们建议用CSS框架来补充教育部门的灾后需求评估框架。 关键词：综合校园安全；减少灾害风险；洪水对学校的影响；洪水风险；印度尼西亚；雅加达；学习恢复；学校中断；学校恢复